Platinum(IV) complex with adamantylamine overcomes intrinsic resistance to cisplatin in ovarian cancer cells - Horváth, Viktor; Blanárová, Olga; Svihálková-Sindlerová, Lenka; Soucek, Karel; Hofmanová, Jirina; Sova, Petr; Kroutil, Ales; Fedorocko, Peter; Kozubík, Alois (Gynecologic oncology, 2006)
OBJECTIVES: The resistance of tumor cells to cisplatin remains a major cause of treatment failure in cancer patients. In this study, the ability of Pt(IV) complex with adamantylamine-LA-12 and its reduced counterpart with lower oxidation state Pt(II)-LA-9 to overcome intrinsic cisplatin resistance was investigated. METHODS: The ovarian adenocarcinoma SK-OV-3 cells were exposed to cisplatin, LA-9, or LA-12 for 72 h and the effects of drug concentrations that caused 10% or 50% inhibition of cell proliferation were determined. After 24-72 h of sustained exposure viability, apoptosis and inhibition of proliferation were analyzed. DNA synthesis and cell cycle analysis were performed simultaneously in order to determine the modulation of cell cycle after platinum complexes treatment. RESULTS: Lung Resistance-related Protein (LRP/MVP) was detected in SK-OV-3 cells but not in the other two ovarian cancer lines with different sensitivity to cisplatin. LRP/MVP overexpression may be an important factor contributing to intrinsic cisplatin resistance. Interestingly, Pt(IV) complex-LA-12 had approximately 2.7-fold lower IC(50) concentration than LA-9 or cisplatin in SK-OV-3 cells. Moreover, LA-12 caused persistent accumulation of cells in S-phase of the cell cycle while LA-9 and cisplatin treatment-induced S-phase arrest was transient and shifted to G(2)/M-phase at later intervals. Apoptosis seemed to be not the dominant type of cell death caused by such the derivatives, but it was the most intensive after LA-12 treatment. CONCLUSIONS: We found strong differences between effects of Pt(IV) complex-LA-12 and Pt(II) derivatives-LA-9 and cisplatin on cytokinetic parameters. Overall, LA-12 but not its reduced Pt(II) counterpart LA-9 is the compound effective in p53 null human ovarian cancer cells and it is able to overcome intrinsic cisplatin resistance in these cells.
Keywords: vault ribonucleoprotein particles; nádorové proteiny; Cell Growth Processes; Vault Ribonucleoprotein Particles; Cell Line, Tumor; Antineoplastic Combined Chemotherapy Protocols; Ovarian Neoplasms; western blotting; DNA nádorová; chemorezistence; poly(ADP-ribosa)polymerasy; Amantadine; Organoplatinum Compounds; Poly(ADP-ribose) Polymerases; nádory vaječníků; amantadin; DNA, Neoplasm; Blotting, Western; lidé; ženské pohlaví; adenokarcinom; Humans; protokoly protinádorové kombinované chemoterapie; Cell Cycle; Neoplasm Proteins; cisplatina; Drug Resistance, Neoplasm; buněčný cyklus; nádorové buněčné linie; Adenocarcinoma; Female; organoplatinové sloučeniny; Cisplatin; buňky - růstové procesy